The Effect of Weather-Induced Internal Migration on Local Labor Markets : Evidence from Uganda - Strobl, Eric; Valfort, Marie-Anne (Oxford University Press on behalf of the World Bank, 2017)
Relying on census data collected in 2002 and historical weather data for Uganda, we estimate the impact of weather-induced internal migration on the probability for non-migrants living in the destination regions to be employed. Consistent with the prediction of a simple theoretical model, our results reveal a larger negative impact than the one documented for developed countries. They further show that this negative impact is significantly stronger in Ugandan regions with lower road density and therefore less conducive to capital mobility: a 10 percentage points increase in the net in-migration rate in these areas decreases the probability of being employed of non-migrants by more than 10 percentage points.